1989
DOI: 10.1073/pnas.86.9.3252
|View full text |Cite
|
Sign up to set email alerts
|

Differential use of termination codons in ciliated protozoa.

Abstract: Sequence analysis of genes in four species of ciliated protozoa and analysis of tRNAs in Tetrahymena has demonstrated that TAG and TAA encode glutamine or glutamic acid in these organisms and TGA is the only stop codon. Thus, it has generally been assumed that all ciliates use a nonuniversal genetic code in which TGA acts as the sole termination codon. We have sequenced the linear DNA molecules that carry an actin gene and a P-tubulin gene from the ciliate Euplotes crassus. These genes are shown to use TAA as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Similarly, differences in the usage of termination codons have been observed in ciliated protozoa (13), and in some ciliates, stop codons are reassigned to sense codons (19). Clearly, the appropriate code can be selected when sequencing clones from a known organism, but choice is more problematic for environmental isolates.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, differences in the usage of termination codons have been observed in ciliated protozoa (13), and in some ciliates, stop codons are reassigned to sense codons (19). Clearly, the appropriate code can be selected when sequencing clones from a known organism, but choice is more problematic for environmental isolates.…”
Section: Resultsmentioning
confidence: 99%
“…This assumption was based on sequence analyses of genes in four genera: Paramecium (1, 2), Tetrahymena (3-7), Stylonychia (8), and Oxytricha (9). Recently this view was challenged by the finding that in Euplotes crassus (10) and Euplotes raikovi (11), UAA is used as a termination codon, indicating that the Euplotids differ in this respect from other ciliates. Here we report on the cDNA and amino acid sequence of pheromone 3 of Euplotes octocarinatus.…”
mentioning
confidence: 99%
“…Alternatively, it has been suggested that a second unusual genetic feature of Euplotes, stop-codon reassignment, is involved in slowing translation and promoting the frameshifts (22). Euplotids have reassigned the UGA stop codon of the universal code so that it now encodes cysteine (16,28). This has occurred, in part, as a result of changes to the single eukaryotic translation release factor 1 protein (eRF1) so that it no longer recognizes the UGA stop codon (9, 21, 34a).…”
mentioning
confidence: 99%